Effect of Indenter Angle on Bearing Performance of Coal and Accompanying Rocks Under Point Load and Characterization of Mechanical Parameters - Qian Wang; Yujiang Zhang; Delong Cui; Guorui Feng; Yunlou Du; Shuai Zhang; Haojie Cheng; Zhengjun Zhang (Energy Science & Engineering)
ABSTRACT Coal, mudstone, sandstone, and limestone, which are common in coal mines, were selected as research objects, and 60°, 90°, and 120° indenters were used to conduct point load tests to study the deformation and failure laws of rocks under point loads. This study identified a process for generating and crushing compacted bodies. As the indenter angle increased, the number of compacted bodies formed decreased significantly, and the stress drop decreased. The ultimate invasion depth upon reaching the failure load decreased as a quadratic function as the indenter angle increased. Under the load of indenter points at different angles, all samples underwent splitting failure along the loading axis. As the indenter angle increased, the indentation diameter increased quadratically. The angle of the indenter had a greater influence on the indentation diameter of low‐strength rocks, and the failure of coal and accompanying rocks was more stable under the action of large‐angle indenters. The point load test data were statistically analyzed. The load intensity of the indenter point at different angles exhibited a linear relationship with the uniaxial compressive strength, tensile strength, and elastic modulus, and the fitting degree was the best when the indenter angle was 120°